2015
DOI: 10.1037/a0038457
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic alliance as a predictor of outcome in dialectical behavior therapy versus nonbehavioral psychotherapy by experts for borderline personality disorder.

Abstract: The purpose of the present study was to explore facets of the client- and therapist-rated therapeutic alliance as predictors of suicide attempts, nonsuicidal self-injury, depression, and introject during the course of 2 psychosocial treatments for borderline personality disorder. A total of 101 women meeting Diagnostic and Statistical Manual of Mental Disorders-IV DSM-IV criteria for borderline personality disorder participated in a randomized controlled trial of dialectical behavior therapy (DBT) versus commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 28 publications
(38 reference statements)
2
56
0
5
Order By: Relevance
“…In the non-ED literature, a study investigating two treatments for borderline personality disorder indicated that alliance was more important for outcome in patients receiving behavioral (i.e., dialectical behavioral therapy) versus nonbehavioral (i.e., community care by experts) treatment (Bedics, Atkins, Harned, & Linehan, 2015). Conversely, one meta-analysis found that alliance was relevant to the outcome of therapy only when that therapy was relatively unstructured (i.e., nonbehavioral) (Crits-Christoph et al, 1991); though other meta-analyses have not replicated this distinction (Horvath et al, 2011).…”
Section: Therapy Typementioning
confidence: 99%
“…In the non-ED literature, a study investigating two treatments for borderline personality disorder indicated that alliance was more important for outcome in patients receiving behavioral (i.e., dialectical behavioral therapy) versus nonbehavioral (i.e., community care by experts) treatment (Bedics, Atkins, Harned, & Linehan, 2015). Conversely, one meta-analysis found that alliance was relevant to the outcome of therapy only when that therapy was relatively unstructured (i.e., nonbehavioral) (Crits-Christoph et al, 1991); though other meta-analyses have not replicated this distinction (Horvath et al, 2011).…”
Section: Therapy Typementioning
confidence: 99%
“…El primer paso en estos tratamientos es el establecimiento de una adecuada alianza terapéutica (Bedics, Atkins, Harned y Linehan, 2015;Briggs et al, 2012;Fukumitsu, 2014;Gabbard, 2002).…”
Section: Discussionunclassified
“…therapeutische Allianz haben wir jedoch nicht gemessen, auch wenn aufgrund der Zertifizierung und des Bestehens eines tagesklinischen DBT-Angebotes über mehr als 5 Jahre eine hohe Identifizierung mit der DBT im Therapeutenteam zu erwarten ist [Swales et al, 2012] und damit dieses in guter Qualität und Stabilität vorliegen sollte. Adhärenz und therapeutische Allianz sind für weiterführende Studien jedoch zu fordern [Bedics et al, 2015].…”
Section: Diskussionunclassified
“…Aber auch in einer randomisierten kontrollierten Studie reduzierten komorbide Dissoziationen während der DBT bei BPS und gleichzeitig vorliegender PTBS deren Therapieerfolg [Kleindienst et al, 2016]. Bedics et al [2015] konnten an 101 Frauen mit einer BPS über eine 1-JahresSpanne zeigen, dass die Stärke der therapeutischen Allianz die Suizidalität beeinflusst und damit auch den Therapieerfolg. Diese Ergebnisse konnten auch Steuwe et al [2017] replizieren.…”
unclassified